1994
DOI: 10.1523/jneurosci.14-02-00897.1994
|View full text |Cite
|
Sign up to set email alerts
|

A functional anatomical analysis of central pathways subserving the effects of interleukin-1 on stress-related neuroendocrine neurons

Abstract: Systemic administration of the cytokine interleukin-1 (IL-1) results in increased secretion of ACTH and corticosterone in rats. The available evidence suggests that the acute effects of IL-1 are exerted ultimately at the level of the hypothalamus to increase corticotropin-releasing factor (CRF) secretion into the hypophyseal portal circulation, and hence the central drive on the pituitary-adrenal system. However, the route(s) and mechanism(s) by which circulating IL-1 gains access to central mechanisms governi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
503
6
6

Year Published

1996
1996
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 635 publications
(548 citation statements)
references
References 70 publications
33
503
6
6
Order By: Relevance
“…Vagal sensory input from the abdomen implicated in the central neural (Wan, et al, 1994), hyperthermic , and hormonal (Fleshner, et al, 1995;Gaykema, et al, 1995;Kapcala, et al, 1996) responses to inflammatory stimuli may have contributed to this response as may the action of circulating mediators on the area postrema (Cunningham et al, 1994). However, Fos appeared in this circumventricular organ only in the rats with the most intense dorsomedullary responses as reported previously during acute inflammation Ericsson, et al, 1994).…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…Vagal sensory input from the abdomen implicated in the central neural (Wan, et al, 1994), hyperthermic , and hormonal (Fleshner, et al, 1995;Gaykema, et al, 1995;Kapcala, et al, 1996) responses to inflammatory stimuli may have contributed to this response as may the action of circulating mediators on the area postrema (Cunningham et al, 1994). However, Fos appeared in this circumventricular organ only in the rats with the most intense dorsomedullary responses as reported previously during acute inflammation Ericsson, et al, 1994).…”
Section: Discussionsupporting
confidence: 63%
“…For example long-term suckling fails to induce Fos in oxytocin-containing neurons (Fenelon et al, 1993). Furthermore, intravenous doses of endotoxin Zhang, et al, 2003) or interleukin-1 (Ericsson, et al, 1994) increase central Fos for about 6 h with a peak at 2 to 3 h. Improved detection of Fos through the use of optimized fixation and antibodies as in the present study may reveal responses of longer duration, but their intensity frequently declines from the initial peak. Sustained expression of Fos in the NTS and ventrolateral medulla does occur in some experimental models of chronic hypertension (Lohmeier et al, 2002;Lohmeier et al, 2003); and, in contrast to the present findings, CRH neurons in the PVH show a sustained increase in Fos mRNA during chronic insulin-induced hypoglycemia (Brown and Sawchenko, 1997).…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Mascarucci et al [53] showed that ip hIL-1β (4 μg/rat ip) increased apparent glutamate release from the nucleus tractus solitarius (NTS), although heat-treated IL-1 also elicited a partial response. [54][55][56]. The structure most markedly affected is the hypothalamic PVN, which contains the cell bodies of the neurons that synthesize CRF involved in the activation of the HPA axis.…”
Section: Effects On Other Neurotransmitters-il-1βmentioning
confidence: 99%